2010
DOI: 10.7326/0003-4819-152-6-201003160-00003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Concurrent Use of Clopidogrel and Proton-Pump Inhibitors

Abstract: Background Proton-pump inhibitors (PPIs) and clopidogrel are frequently co-prescribed though the benefits and harms of their concurrent use are unclear. Objective To examine the association between concurrent PPI and clopidogrel use and the risks for gastroduodenal bleeding hospitalizations and serious cardiovascular disease. Design Retrospective cohort study that used automated data to identify patients who received clopidogrel between 1999 through 2005 following hospitalization for coronary heart disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
182
0
19

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(208 citation statements)
references
References 43 publications
6
182
0
19
Order By: Relevance
“…2,3) Some of the studies confirmed an interaction between clopidogrel and PPI. 4,5,[8][9][10] Kyeong, et al found that the P2Y12 reaction unit (PRU) of omeprazole treated subjects was signifi cantly higher than that of the omeprazole untreated subjects and the percentage inhibition decreased in the omeprazole treatment versus no omeprazole treatment. 4) Moreover, it has been found that patients taking clopidogrel plus a PPI had a higher risk of hospitalization for recurrent acute coronary syndrome compared with patients taking clopidogrel without a PPI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3) Some of the studies confirmed an interaction between clopidogrel and PPI. 4,5,[8][9][10] Kyeong, et al found that the P2Y12 reaction unit (PRU) of omeprazole treated subjects was signifi cantly higher than that of the omeprazole untreated subjects and the percentage inhibition decreased in the omeprazole treatment versus no omeprazole treatment. 4) Moreover, it has been found that patients taking clopidogrel plus a PPI had a higher risk of hospitalization for recurrent acute coronary syndrome compared with patients taking clopidogrel without a PPI.…”
Section: Discussionmentioning
confidence: 99%
“…8) Loss-of-function polymorphisms in the CYP450 genes may also reduce clopidogrel metabolism and are therefore likely to intensify interactions between drugs metabolized by the CYP450 system. 9,10) Thus, The United States Food and Drug Administration (FDA) and the European Medicines Agency have recommended that physicians avoid the use of omeprazole in all patients taking clopidogrel. 12,13) Various studies have examined the impact of the FDA warnings on the prescription pattern of some drugs such as droperidol cisapride, antipsychotics and antidepressants, and glucose lowering drugs.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with serious coronary heart disease treated with clopidogrel, concurrent PPI use was associated with reduced incidence of hospitalizations for gastroduodenal bleeding (Ray et al. 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, where particular outcomes are infrequent, observational studies may be FUNCTIONAL GI DISORDERS ucm191169.htm ), van Boxel et al found no diff erence in apparent cardiovascular risk among the PPIs they examined -including those discouraged by the FDA. Others have similarly found no apparent diff erence among the various PPIs with respect to rates of cardiovascular events in clopidogrel users ( 3,7 ). Th erefore, a patient who requires PPI co-therapy should be prescribed the agent that he or she fi nds most accessible and aff ordable.…”
mentioning
confidence: 97%